PROGNOSTIC VALUE OF STRESS ECHOCARDIOGRAPHY IN PATIENTS WITH ANGINA PECTORIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
IHD continues to be one of the main problems of modern medicine. This leads to an increase in the percentage of coronary deaths among men and women. In the diagnostic algorithm for coronary artery disease, stress echocardiography (stress echocardiography) is required before selective coronary angiography. at the moment this is the best (cheapest and safest) imaging method among non-invasive methods for detecting coronary heart disease (CHD). It has similar diagnostic accuracy and predictive value to radionuclide loading methods, but is much less expensive, safer for the environment, and has less radiation exposure to the patient and physician.